Catutisme dan Perjuangan: Korupsi Pengumpulan Padi di Jawa Tengah pada Masa Revolusi, 1945-1949 - Julianto Ibrahim (Universitas Gadjah Mada, 2022)
This article discusses corruption actions committed by the officials of the People’s Food Supervision (PMR - Pengawasan Makanan Rakyat), a government body assigned to collect rice donations from the population in Central Java during the revolution period. Those officials swindled and took a certain portion of the collected rice for personal use, while originally it was supposed to be distributed to the fighters and starving people. Rice collecting is one of Indonesia’s government endeavors to obtain the needed funds to sustain the revolution. The practice was actually a continuation of the one introduced during the Japanese Colonial Period. The collected rice was used as a logistics supply for fighters in the front. Part of it was also shared with people in need. To collect the rice efficiently, the government pointed out several boards, including PMR. Unfortunately, The PMR officials who were responsible for the task on behalf of the Republican government corrupted the rice.